Linking High-Performance Human Resource Management Practices to Employee Readiness for Change: The Roles of Job Satisfaction and Affective Commitment — A Systematic Literature Review - Grandis Harlandi Choirul Nisa; Nurul Safitri (Politeknik Siber Cerdika Internasional, 2026)
Background: High-performance human resource management practices (HPHRMPs), also known as high-performance work systems (HPWSs), have been extensively studied as strategic human resource management configurations that improve organizational performance. However, their role in facilitating employee readiness for change, especially through attitudinal mediators, has not been systematically explored. Objective: This systematic literature review integrates empirical evidence on the relationship between HPHRMPs/HPWSs and employee readiness for change, with particular emphasis on the mediating roles of job satisfaction and affective commitment. Methods: Following the PRISMA 2020 guidelines, a comprehensive search of the Scopus database identified 210 records across five targeted searches. After removing 21 duplicates, 189 records were screened based on titles and abstracts, and 38 articles were selected for full-text review. Thirty-five studies met all eligibility criteria and were included in the final narrative synthesis. Results: Three main pathways were identified: (1) HPHRMPs/HPWSs had a direct positive effect on readiness for change; (2) indirect effects occurred through job satisfaction; and (3) indirect effects were mediated through affective commitment. HPHRMPs/HPWSs practices, particularly training and development, employee involvement, and selective staffing, consistently foster positive employee attitudes and motivate employees to embrace organizational change. Conclusion: HPHRMPs/HPWSs enhance readiness for change through both direct and indirect mechanisms. Job satisfaction acts as an emotional bridge, while affective commitment provides a deeper psychological attachment that sustains readiness for change over time. Organizations seeking to manage change effectively should invest in a comprehensive HPHRMPs/HPWSs bundle as a proactive strategy for developing change-ready talent.